The raspberry locus encodes Drosophila inosine monophosphate dehydrogenase. - Slee, R.; Bownes, M. (Molecular and General Genetics, 1995)
Investigation of an enhancer-trap line exhibiting testis-specific beta-galactosidase expression led to the isolation of the Drosophila gene encoding inosine monophosphate dehydrogenase (IMPD), the rate-limiting enzyme in guanine nucleotide synthesis, which has been implicated in cell cycle control and malignant transformation. Northern and in situ hybridization analysis demonstrated that the gene has a complex expression pattern involving several independently regulated transcripts. Two ubiquitous, but highly ovary enriched, transcripts of 2.5 and 1.9 kb are expressed in the nurse cells and delivered to the oocyte, whilst a 0.9 kb transcript is found exclusively in the testis. The 2.5 kb transcript encodes a 58 kDa protein, which is highly similar in length and sequence to mouse and human IMPDs and is presumably required for GTP synthesis during early embryogenesis. Over-expression of this cDNA in Escherichia coli yielded a product of the predicted size, which was demonstrated to possess IMPD activity in a spectrophotometric assay. The coding capacity of the other transcripts is currently uncertain. We present evidence that IMPD is the product of the raspberry (ras) locus at 9E and the functions of the gene are discussed in relation to the phenotypes of ras mutants.